2020
DOI: 10.1007/s00467-020-04743-9
|View full text |Cite
|
Sign up to set email alerts
|

Silent and dangerous: catheter-associated right atrial thrombus (CRAT) in children on chronic haemodialysis

Abstract: Background Catheter-associated right atrial thrombus (CRAT) is a recognised complication of central venous catheter (CVC) use for haemodialysis (HD) patients. Methods This was a single-centre retrospective longitudinal observational study of consecutive children aged 6 months–18 years over a 7-year period receiving in-centre chronic HD. Echocardiograms as per routine cardiac surveillance were performed 6 months or earlier given clinical concerns. Results Sixty-five children, 36 boys (55.4%), median (IQR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…CRAT is often insidious and a potentially life-threatening complication that may arise in association with any CVC. However, it predominantly presents in cases involving tunneled HD catheters, typically emerging 12 weeks post-catheter insertion 1 . There is a paucity of data describing the occurrence of HDCRAT in the context of temporary HD catheters used for acute renal replacement therapy in critically ill medical ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRAT is often insidious and a potentially life-threatening complication that may arise in association with any CVC. However, it predominantly presents in cases involving tunneled HD catheters, typically emerging 12 weeks post-catheter insertion 1 . There is a paucity of data describing the occurrence of HDCRAT in the context of temporary HD catheters used for acute renal replacement therapy in critically ill medical ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there has been a noticeable paradigm shift in the application of TEE 14 , 15 , 16 . This shift has extended its utility beyond cardiologists and cardiothoracic anesthesiologists, to employment by intensivists at the bedside 1 . Notably, Lau et al have substantiated that intensivist-performed limited TEE exhibits diagnostic accuracy equal to that achieved by cardiologists 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal treatment for PE due to CVC-related thrombosis is still unknown, but a conservative approach in terms of anticoagulant and systemic thrombolytic therapy has been recently proposed for children on chronic haemodialysis ( 22 ). This strategy neither lead to atrial thrombus resolution, nor restoration of pulmonary circulation in both of the presented patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the catheter or the guiding medium may cause acute mechanical friction damage to the vascular intima during insertion 12 , 13 . Moreover, factors such as the position or morphology of the catheter tip, the size of the catheter relative to the central vein, and changes in right atrial hemodynamics are also associated with catheter-related complications such as CVS 14 16 . In addition, imaging confirmed that the catheter had sustained regular or irregular multidirectional displacement in the blood vessel because of blood flow, heartbeat, breathing, body position, and regular negative pressure suction produced by the blood pump of the dialysis machine 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%